Cystic neutrophilic granulomatous mastitis: The Cleveland Clinic experience with diagnosis and management. Issue 1 (17th November 2018) - Gautham, Ila; Radford, Diane M.; Kovacs, Christopher S.; Calhoun, Benjamin C.; Procop, Gary W.; Shepardson, Laura B.; Dawson, Andrea E.; Downs‐Kelly, Erinn P.; Zhang, Gloria X.; Al‐Hilli, Zahraa; Fanning, Alicia A.; Wilson, Deborah A.; et al.
Abstract: Granulomatous mastitis is an uncommon inflammatory disease that typically presents with painful breast lesions. Recent publications have brought to light a specific subset of granulomatous mastitis patients with a distinct histological pattern of disease termed, "cystic neutrophilic granulomatous mastitis" (CNGM). Although many cases of granulomatous lobular mastitis have been thought to be idiopathic, this rare subset of an uncommon disease has been linked to infections with Corynebacterium species. Herein, a cohort of CNGM patients from a large, tertiary care, North‐American, academic medical center is presented. Correlative demographic, clinical, radiographic, pathologic, microbiologic, management, and outcomes data are provided. Collaborative communication between specialists to accurately diagnose and manage these patients is essential to decreasing potential morbidity.